Epitaxial growth of (Ba0.7Sr0.3)TiO3 thin films on GdScO3 substrates by magnetron sputtering - Ye, Dongjin; Nie, Penghao; Jiang, Shuwen; Zhang, Wanli (AIP advances, 2023)
Epitaxial growth of Ba0.7Sr0.3TiO3 (BST70) thin films on GdScO3 (GSO) substrates had been realized using the radio frequency magnetron sputtering system with the epitaxial alignment [001]BST70||[110]GSO and [010]BST70||[001]GSO. Reciprocal space mapping and transmission electron microscope results confirm the epitaxial growth without an impurity phase at the interface. The Fourier-filtered image shows that the BST70 thin film grew well with few dislocations. The out-of-plane parameter of the as-deposited film was elongated due to strain, which was induced by the differences in the thermal expansion coefficients between the film and the substrate, and oxygen vacancies. The highly strained as-deposited BST70 films could be relaxed by the post-annealing procedure at 800 °C in an O2-rich atmosphere for better epitaxial quality.